The usage of Maxwell fractional equations for the investigation of the waveguide processes - Maksyuta, M.V.; Slinchenko, Yu.A.; Grygoruk, V.I. (Вопросы атомной науки и техники, 2016)
By means of nabla operator written down with using both of some differential operators with integer orders and
fractional differential Caputo operators, gradient, divergence and rotor operators are determined, it is checked up the
fulfillment of vector relations in fractional vector analysis, fractional Green’s, Stocks’ and Ostrogradsky-Gauss’
formulas. For a specific expression of nabla operator (nabla components along х and у axes have a unit order and
along z axis, correspondingly, a fractional value in the interval from zero till unit) Maxwell’s fractional equations are written down. Based on the following from them some fractional wave equations, dissipative and polarization processes at electromagnetic waves distribution both in rectangular (planar) and in cylindrical waveguide structures are analyzed. С помощью оператора набла, записанного с одновременным использованием как дифференциальных
операторов с целочисленными порядками, так и дробных дифференциальных операторов Капуто,
определяются операторы градиента, дивергенции и ротора, проверяется выполнимость векторных
соотношений дробного векторного анализа, дробных формул Грина, Стокса и Остроградского-Гаусса. Для
конкретного выражения оператора наблы (компоненты наблы вдоль осей х и у имеют единичный порядок, а
вдоль оси z, соответственно, дробное значение в интервале от нуля до единицы) записываются дробные
уравнения Максвелла. На основе следующих из них дробных волновых уравнений анализируются
диссипативные и поляризационные процессы при распространении электромагнитных волн как в
прямоугольных (планарных), так и в цилиндрических волноводных структурах. За допомогою оператора набли, записаного за одночасного використання як диференціальних операторів
з цілочисельними порядками, так і дробових диференціальних операторів Капуто, визначаються оператори
градієнта, дивергенції та ротора, перевіряється виконуваність векторних співвідношень дробового
векторного аналізу, дробових формул Гріна, Стокса та Остроградського-Гауса. Для конкретного виразу
оператора набли (складові набли уздовж осей х та у мають одиничний порядок, а уздовж осі z, відповідно,
дробове значення в інтервалі від нуля до одиниці) записуються дробові рівняння Максвелла. На основі
випливаючих із них дробових хвильових рівнянь аналізуються дисипативні та поляризаційні процеси при
розповсюдженні електромагнітних хвиль як у прямокутних (планарних), так і в циліндричних хвилеводних
структурах.